Implementasi ISO 9126 pada Aplikasi SiGezel dengan Fitur Reservasi untuk Loyalitas Pelanggan Café - Auliya Apriwiguna; Achmad Baroqah Pohan; Besus Maula Sulthon; Sri Wasiyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Café Gezellig in East Jakarta still relies on manual reservation methods through WhatsApp and Instagram, leading to operational inefficiencies, delayed confirmations, and low customer engagement. This study aims to develop a web-based reservation system integrated with a point-based Customer Relationship Management (CRM) feature to enhance customer loyalty. The development method used is Rapid Application Development (RAD), which involves users in every iteration stage, including baristas, cashiers, managers, and regular customers. The system was built using PHP with the Laravel framework and MySQL database, covering modules for table and room reservations, payment management, and loyalty point management. Software quality was evaluated using the ISO 9126 standard through a Likert-scale questionnaire (1–5) across six aspects, completed by five respondents from the café’s internal team (owner, manager, cashier, reservation admin, and waiter). The test results show functionality at 88%, reliability at 87.5%, usability at 86%, efficiency at 88.89%, portability at 88.75%, and maintainability at 93.75%, with an overall average score of 88.81% categorized as good. These findings indicate that the SIGEZEL system is feasible to replace manual processes, simplify reservation confirmations, improve staff operational efficiency, and support customer management through an integrated point program, thereby strengthening customer loyalty and increasing the likelihood of repeat purchases.